2020
DOI: 10.1038/s41523-020-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in assessing stromal tumor infiltrating lymphocytes (sTILs) in breast cancer

Abstract: Stromal tumor-infiltrating lymphocytes (sTILs) are important prognostic and predictive biomarkers in triple-negative (TNBC) and HER2-positive breast cancer. Incorporating sTILs into clinical practice necessitates reproducible assessment. Previously developed standardized scoring guidelines have been widely embraced by the clinical and research communities. We evaluated sources of variability in sTIL assessment by pathologists in three previous sTIL ring studies. We identify common challenges and evaluate impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 48 publications
5
116
0
Order By: Relevance
“…We observed an excellent interrater agreement score between our panel of four expert pathologists. In an accompanying paper 7 we demonstrate using data from three RING studies of the TIL Working Group that the concordance achieved using a riskmanagement approach as detailed in this study is substantially higher than observed outside this risk-management perspective as observed in the three RING studies and in other published studies 19,20 . However, our sample size is small and the four pathologists in the current study were trained and experienced in the scoring of sTILs in breast cancer.…”
Section: Advantages and Limitations Of A Web-based Risk-mitigation Womentioning
confidence: 51%
See 1 more Smart Citation
“…We observed an excellent interrater agreement score between our panel of four expert pathologists. In an accompanying paper 7 we demonstrate using data from three RING studies of the TIL Working Group that the concordance achieved using a riskmanagement approach as detailed in this study is substantially higher than observed outside this risk-management perspective as observed in the three RING studies and in other published studies 19,20 . However, our sample size is small and the four pathologists in the current study were trained and experienced in the scoring of sTILs in breast cancer.…”
Section: Advantages and Limitations Of A Web-based Risk-mitigation Womentioning
confidence: 51%
“…Furthermore, sTILs correlate with outcome after immune checkpoint blockade in metastatic TNBC [4][5][6] . The readout of sTILs, however, can be challenging impeding its effective use as a biomarker and its usage in the clinic 7 . The International Immuno-Oncology Biomarker Working Group (hereafter called the TIL Working Group) has provided guidelines for the scoring of sTILs in breast cancer 8 , and the St. Gallen Breast Cancer Conference of 2019 endorsed sTILs being routinely characterized in TNBC and reported according to these guidelines 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though TILs will require validation in accordance with regulatory standards prior to being clinically recommended as a predictive biomarker for response to ICI, TILs ≥5% have been shown to be predictive of response to pembrolizumab on the exploratory analysis of the randomized phase III KEYNOTE-119 clinical trial [57]. In addition, TILs have been analytically validated, with three ring studies showing reliable interreader reproducibility [97][98][99], and have the advantage of being easily assessed on a simple H&E slide with an existing standardized method that is available to the pathology community though numerous publications and at the TIL-WG website [2,89]. In a recent publication, an analysis of the most discordant cases on the ring studies identified possible pitfalls for scoring TILs, including technical factors, sample heterogeneity, variability in defining tumor boundaries, differentiating lymphocytes from mimics, and limited stroma for evaluation.…”
Section: Use Of Multiple Pd-l1 Assays For a Single Analytementioning
confidence: 99%
“…In a recent publication, an analysis of the most discordant cases on the ring studies identified possible pitfalls for scoring TILs, including technical factors, sample heterogeneity, variability in defining tumor boundaries, differentiating lymphocytes from mimics, and limited stroma for evaluation. Approaches to avoid these pitfalls have been covered in the publication, and associated educational resources are available at the TIL-WG website [89,97]. Once pathologists score TILs in their daily practice for prognostic purposes, this information will already be present in the report.…”
Section: Use Of Multiple Pd-l1 Assays For a Single Analytementioning
confidence: 99%
“…Despite the acceptance of sTILs as prognostic and predictive biomarkers, the assessment of sTILs is challenging within the complex landscape of cancer, which results in scoring discordance due to the heterog e n e i t y o f t h e d i s t r i b u t i o n o f l y m p h o c y t e s . Discrepancies also arise from the lack of consensus about the precise boundary of tumors, variable presence of tumor-associated stroma, associations of lymphocytes with other microanatomic structures, presence of other kinds of immune cells [50,65]. Even though these kinds of variations during the evaluation of sTILs have mitigable effects in estimating risk in early TNBC, multiple areas are scored and averaged during the evaluation of sTILs to improve consistency and minimize the effects of observer variability, scoring discrepancies, and cutoffs that could affect treatment selection [50,65].…”
Section: Ensemble Pathomics For Advanced Tumor-tils Analysesmentioning
confidence: 99%